Security in Wireless Body Sensor Network : A Multivocal Literature Study - Najm Us, Sama; Kartinah, Zen; Mamoona, Humayun; Noor Zaman, Jhanjhi; Atiq Ur, Rahman (MDPI, 2022)
: The wireless body sensor network (WBSN) is a wireless communication that might enable 24/7 patient monitoring and health findings through the online platform. Although BSN design is becoming simpler, building a secure BSN seems to be more challenging than designing conventional solutions, and the recent study provides little guidance to designers and developers. The proposed study summarizes the multivocal literature study of security mechanisms for BSN. The investigation found 10,871 academic publications and 697 grey content; duplicates were removed, and selection criteria were employed, resulting in 73 academic papers and 30 grey publications. Various conventional security techniques, scope, and security contexts were used to classify the stated security solutions within each publication. It was crucial to inquire about the frequency of publications, research methods, security mechanisms, and contexts to answer the proposed questions. Our survey concludes that security methods and assessments are categorized into 15 categories, with the most frequently referenced being authentication and authorization; the majority of strategies concentrate on preventing and mitigating security breaches, with a limited number of works focusing on detection and recovery; and the techniques used to conduct the survey vary between the two types of publications. This evaluation might be the first step toward making the BSN platform more consistent by giving professionals and researchers a complete set of security strategies and methods. Experts will apply these solutions to fix security issues while establishing a trustworthy BSN after they have been identified through the process of discovering the most commonly utilized security solutions.